Kewirausahaan Yang Beretika: Peran Akhlak Islami Dalam Membangun Kepercayaan dan Keberlanjutan - Al Anshari; Jaharuddin Jaharuddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The application of Islamic moral values ​​in entrepreneurship, especially the principles of justice, has a significant impact on the sustainability and blessing of the business. This research identifies various important aspects of implementing the principles of justice, including increasing customer loyalty, strengthening business relationships, and creating social harmony. Although there are challenges in implementation, such as market pressures and intense competition, business ethics education and regulatory support can help Muslim entrepreneurs to adhere to Islamic moral principles. The research results show that the application of Islamic morals not only provides economic benefits, but also creates positive social and spiritual impacts, thereby ensuring sustainability and blessings in the long term.